The rhetorical strategies of the Quran - Kusen Kusen; Zainal Rafli; Emzir Emzir (Universitas Ahmad Dahlan, 2020)
This research was aimed to analyze translation strategies in the Quran. The content analysis method with the qualitative approach used in the research. The data in this study are words, phrases, sentences in the text of the translation of the ayahs of the Glorious Qur'an surah Albaqarah ayah 1 to ayah 286. The procedure applied in the analysis of the data is the inductive model procedure. The development model of the rhetorical strategies used by Toulmin model. The results showed the model development strategies IV (G.W. B àC). The other model used the alternative model. It is another model appeared aside from what Toulmin has given, W. B àC. Model W. B àC is used as much as 7 times or of 17.5%. The next strategy model that also is a widely used is alternative models W.B. Q àC and the model V is used 5 times (12.5%). Next is the model of strategy III (Ground + Warrant àClaim), used four times or by 10% and the model I (Ground àClaim), model II (Ground-n àn-Claim), model W àC, and model W. R àC each used 1 time or amounting to 2.5%. All of the claims are expressed using complex rhetorical strategies. A claim supported by more than one fact either parallel or not parallel. There are few facts and data (ground), reinforced with a justification or validation data (warrant), reinforced again with power support (backing support) to strengthen one or more than one claim.